Treatment of respiratory impairment in patients with motor neuron disease in the Netherlands: patient preference and timing of referral. Issue 12 (9th February 2013) - Raaphorst, J.; Tuijp, J.; Verweij, L.; Westermann, E. J. A.; van der Kooi, A. J.; Gaytant, M. A.; van den Berg, L. H.; de Visser, M.; Kampelmacher, M. J.
Abstract : Background and purpose: We assessed the first evaluation at a large ventilation clinic in the Netherlands to: (i) determine what proportion of patients with motor neuron disease would benefit from earlier referral; and (ii) examine the patient preferences regarding ventilatory support. Methods: Observational study at a single centre with a catchment area of 7.6 million inhabitants. Data on disease status, the referral process and patients' preferences regarding ventilatory support were collected during the first home ventilation services (HVS) assessment and analysed for correlation with the presence of daytime hypercapnia and suspected nocturnal hypoventilation. The latter conditions require immediate (within 48 h) or subacute (within 3 weeks) initiation of ventilatory support. Results: Vital capacity (in percentage of predicted value, VC%pred) was assessed by referring physicians in 84% of the 217 referred patients; the mean VC%pred was 69% (SD 16). One‐hundred and ninety‐one patients attended the first HVS assessment without ventilatory support, at a median of 21 days following referral: 18% had respiratory failure (daytime hypercapnia), 19% had normocapnia but were suspected of nocturnal hypoventilation, and 63% had normocapnia without symptoms. Following the HVS assessment, 25 patients (13%) declined home mechanical ventilation; this occurred more often in patients with (14/70) compared with patients without respiratory impairment (11/121; P  < 0.05). Conclusion: A meaningful proportion of patients who desire ventilatory support are referred to a ventilation clinic after already developing respiratory failure. Future studies could examine means, including more sensitive respiratory measures, to detect those patients who could benefit from earlier referral. Abstract : Click here to view the accompanying paper in this issue.